Salacia chinensisexerts its antidiabetic effect by modulating glucose-regulated proteins and transcription factors in high-fat diet fed-streptozotocin-induced type 2 diabetic rats - Erten, Fusun; Orhan, Cemal; Tuzcu, Mehmet; Er, Besir; Defo Deeh, Patrick Brice; Şahin, Nurhan; Şahin, Kazım (Wiley, 2020)
This study aimed to investigate the properties ofSalacia chinensis(Celastraceae, SC) and its molecular mechanism in the type 2 diabetic rats. Forty-two Wistar rats were divided into six groups (n = 7): control, SC (100 mg/kg,per os), high-fat diet (HFD), HFD + SC (100 mg/kg), HFD + streptozotocin (STZ, 40 mg/kg, i.p.), and HFD + STZ+SC. SC decreased serum glucose, insulin, triglycerides, free fatty acid, and malondialdehyde levels, but increased serum total antioxidant capacity (0.33 +/- 0.02 versus. 0.79 +/- 0.03), compared with the untreated group (p < .001). Additionally, SC elevated the expression of glucose-regulated proteins GLUT2, PPAR-gamma, p-IRS, and Nrf2, but downregulated NF-kappa B in the liver and kidney (p < .001). In conclusion, SC could improve insulin resistance by modulation of glucose-regulated proteins and transcription factors in diabetic rats. Practical applications Present data has contributed to the current ethnomedicinal benefits of SC, through which the SC intake regulated the carbohydrate metabolism and increased the antioxidant capacity. The balance of transcription factors can mediate these efficacies partially and various key proteins involved in energy metabolism, along with oxidative stress and insulin sensitivity.
Keywords: diabetes; glucose transporters; oxidative stress; Salacia; transcription factors